2022
DOI: 10.1002/cac2.12388
|View full text |Cite
|
Sign up to set email alerts
|

Elevated neutrophil extracellular traps by HBV‐mediated S100A9‐TLR4/RAGE‐ROS cascade facilitate the growth and metastasis of hepatocellular carcinoma

Abstract: Background: Neutrophil extracellular traps (NETs) are considered significant contributors to cancer progression, especially metastasis. However, it is still unclear whether NETs are involved in hepatitis B virus (HBV)-related hepatocarcinogenesis and have potential clinical significance during evaluation and management for hepatocellular carcinoma (HCC). In this study, we aimed to investigate the functional mechanism of NETs in HBV-related hepatocarcinogenesis and their clinical significance.Methods: A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Reported mechanisms include that S100A9 enhances cancer stem-like properties of hepatocellular carcinoma [ 42 ]. Activation of RAGE/TLR4-ROS signaling pathway leads to the formation of Neutrophil extracellular traps (NETs) that promote HCC growth and metastasis [ 43 ]. Depletion or pharmacological inhibition of S100A9 significantly inhibited HCC growth and metastasis ability [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reported mechanisms include that S100A9 enhances cancer stem-like properties of hepatocellular carcinoma [ 42 ]. Activation of RAGE/TLR4-ROS signaling pathway leads to the formation of Neutrophil extracellular traps (NETs) that promote HCC growth and metastasis [ 43 ]. Depletion or pharmacological inhibition of S100A9 significantly inhibited HCC growth and metastasis ability [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that PI3Kγ is involved in regulating NETs formation during AAA, the molecular mechanism is still poorly understood. Previous studies have shown that reactive oxygen species (ROS) is an important inducer regulating the formation of NETs 45 , and NADPH oxidase enzyme 2 (NOX2) is the key enzyme that produces ROS to mediate the formation of NETs 46 . However, our data showed that PI3Kγ blockade reduced the expression of NETs, but not decreased the upregulation of NOX2 upon LPS stimulation, and had a synergistic effect when combined with NOX2 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil extracellular traps enable to elicit filopodia formation and cell motility in CRC cells dependent upon the activation of EMT process, eventually resulting in the metastatic development of CRC 55 . Neutrophil extracellular traps facilitate the growth and metastasis of HCC, which are primarily dominated by enhanced angiogenesis, EMT‐associated cell migration, matrix metalloproteinases (MMPs)‐based extracellular matrix (ECM) degradation, and NET‐elicited cell trapping 56 . Inhibiting NET production by DNase I potently abrogates the NETs‐evoked HCC growth and metastasis.…”
Section: Netosis In Cancer Metastasismentioning
confidence: 99%